New gait performance indices and cognitive functions: a pilot study on correlation in people with Parkinson’s disease - Cocco, Elena Sofia; Thouant, Carrie-Louise; Pietrosanti, Luca; Infarinato, Francesco; Manzia, Carlotta Maria; Romano, Paola; Torcisi, Raimondo Stefano Maria; Franceschini, Marco; Verrelli, Cristiano Maria; Pournajaf, Sanaz (Frontiers in Human Neuroscience, 2025)
Parkinson’s disease (PD) is the second most common neurodegenerative disease in the world and involves impairment of both motor and cognitive functions, significantly affecting the quality of walking and consequently the quality of life of people affected by this disease. This study analyzed the relationship between gait alterations and cognitive deterioration, using validated clinical tests and an innovative indicator, the φ-bonacci gait number, which quantifies gait harmonicity, symmetry, and consistency. Kinematic data collected during the 6-Minute Walk test on 19 people with PD (pwPD) and 15 healthy adults were analyzed. The results highlighted a significant negative correlation between gait harmonicity and cognitive performance (φ-bonacci gait number—Time Up and Go Dual Task; r = 0.797, p < 0.05). Finally, mediation analysis showed that global cognitive function (MoCA) indirectly influences gait harmonicity through TUG-DT. The results suggest that gait in pwPD is strongly modulated by executive-attentional functions, supporting its cognitive modulation rather than a purely automatic nature. This study allowed to explore the complex relationship between cognitive functions and the motor system, deepening how these interactions influence and refine motor behavior. Therefore, rehabilitation programs combining motor exercises and cognitive training could be more effective in improving gait quality, reducing the risk of falls, and improving person’s quality of life.